Regional developments: Central Asia - Akramov, Kamiljon T.; Djumaboev, Kakhramon; Romashkin, R. (2022)
Central Asia section of Global food policy report highlights regional developments, climate change and its impact on food systems in terms of water use in the region. Moreover, provides options for crop diversification to mitigate malnutrition and role of water saving technologies for adapting climate change impacts.